Case report: Short-term psychotherapy for alexithymia in a patient with generalized anxiety disorder - Wang, Yufei; Cao, Jinya; Wei, Jing (Frontiers in Psychiatry, 2024)
Alexithymia is common among patients with generalized anxiety disorder (GAD) and may negatively affect the efficacy of treatment. This case report described a sole short-term psychotherapy focusing on alexithymia for a GAD patient. The intervention extends over 3 weekly 50-minute sessions and incorporates components of: (a) understanding the basic categories of emotions and the importance of processing them consciously and building one's own vocabulary of emotions; (b) developing skills in identifying and labeling emotions and learning to register both positive and negative emotions in daily life; (c) observing and interpreting emotion-related body sensations and learning to get in touch with, be empathetic to, and take care of one's own inner feelings in daily life. The Hamilton Rating Scale for Depression (HRSD), Hamilton Anxiety Rating Scale (HAMA), and Toronto Alexithymia Scale (TAS) were used to evaluate depression, anxiety, and alexithymia before and after the sessions. The results suggested that the treatment was not only effective in reducing alexithymia helping the patient to clarify, identify and describe her feelings, but also effective in reducing anxiety and depression.